Constitutional Foundations of Family Policy - Sobczyk, Pawel (Demographic Challenges in Central Europe: Legal and Family Policy Response, 2024)
Family policy comprises ‘the totality of legal norms, actions, and measures launched by the state in order to create appropriate conditions for the family to come into being, to develop correctly, and to fulfil all socially important functions’. Owing to the hierarchical structure of modern legal systems, a special part of family law should be attributed to the Constitution as a fundamental law, normalising the foundations of the state system and the legal status of its citizens, enacted in a special procedure. Given their level of generality, the norms contained in the Constitution as the fundamental law of the state require clarification and elaboration in lower-level Acts, most often in ordinary laws and executive Acts issued by executive authorities. This chapter aims, first, to determine if and what the constitutional basis of family policy is in the Central European countries of Croatia, the Czech Republic, Poland, Romania, Serbia, Slovakia, Slovenia, and Hungary. Second, the chapter undertakes a decoding of the constitutional provisions on the protection of the family, marriage, children, and the mother before and after childbirth in these countries to find common solutions for Central European constitutionalism in family policy. Third, an analysis of the constitutional provisions of the above-mentioned countries seeks to determine an optimal model from the perspective of the implementation of family policy and its fundamental goal of stabilising and supporting family life by meeting the needs of families, and (perhaps) to establish a model for a ‘constitutional family policy’ for Central Europe.Keywords: Child, constitution, demography, family, family policy